60.3k views
2 votes
Ax+bx-c=0 x= _/(a __)

User Yegeniy
by
5.4k points

2 Answers

3 votes

x =
(c)/(a+b)

given ax + bx - c = 0 ( add c to both sides )

ax + bx = c ( take out a common factor of x on the left side )

x(a + b) = c ( divide both sides by (a + b) )

x =
(c)/(a+b)


User Shadman Anwer
by
5.6k points
4 votes
ax+bx−c=0

Step 1: Add c to both sides.

ax+bx−c+c=0+c

ax+bx=c

Step 2: Factor out variable x.

x(a+b)=c

Step 3: Divide both sides by a+b.

x(a+b)a+b=ca+b

x=ca+b

User Warwick Masson
by
5.5k points